Quantum Adaptivity in Biology : From Genetics to Cognition /: From Genetics to Cognition. (2015) - Asano, Masanari; Khrennikov, Andrei; Ohya, Masanori; Tanaka, Yoshiharu; Yamato, Ichiro
No abstract available